Unique case of central retinal artery occlusion secondary to COVID-19 disease. (2020) - Acharya, Sudeep; Diamond, Matthew; Anwar, Shamsuddin; Glaser, Allison; Tyagi, Priya
Abstract: SARS-COVID-2 has been noted to be associated with neurological symptoms and complications including stroke. Hypercoagulability associated with COVID-19 has been described as a "sepsis-induced coagulopathy" and may predispose to spectrum of thromboembolic events. We present a unique article of isolated central retinal artery occlusion secondary to SARS-COV 2.